Long‐Term Operation of Perovskite‐Catalyzed Bifunctional Air Electrodes in Rechargeable Zinc‐Air Flow Batteries. Issue 4 (31st October 2018) - Pichler, Birgit; Mayer, Kurt; Hacker, Viktor
Abstract: Rechargeable zinc‐air flow batteries are investigated as promising stationary energy storage system due to compact system design and low cost materials. Bifunctional air electrodes employing a La0.6 Sr0.4 Co0.2 Fe0.8 O3 perovskite catalyst for O2 ‐reduction and O2 ‐evolution are manufactured in small scale (4 cm 2 ) and in up‐scaled sizes (50–55 cm 2 ) and tested in unit cell configuration with flowing electrolyte. Stable operation of 1000 h is achieved in the small set‐up with an overall 1800 h of operation over 700 cycles at high voltage efficiencies of >50 % (air electrode) at 50 mA cm −2 . The up‐scaled flow cell reaches nearly the same performance for 320 h and 130 h, respectively, proving the successful scale‐up. Slowly decreasing hydrophobicity is found to be the main reason of initially increasing but then decreasing performance. This is confirmed by electrochemical impedance spectroscopy. Although many problems are suppressed with flowing electrolyte, zinc morphology proves to be the major challenge especially in larger cells in long‐term operation of a few hundred hours. Abstract : One more cycle : La0.6 Sr0.4 Co0.2 Fe0.8 O3 perovskite is implemented as highly active bifunctional catalyst in optimized air electrode architecture and reaches 1000 h (500 cycles) of stable performance at 50 mA cm −2 (see picture). Up‐scaled 50 cm 2 ‐sized zinc‐air cells are investigated by means of electrochemical impedance spectroscopy and operated for 300 h. Loss of hydrophobicity is found to be the main reason for slowly decreasing performance of the air electrode.